(untitled) (Research, Society and Development, 2022)
High performance sport provides changes in intensities and causes oscillations in the athlete’s temperature, as well as different sensations of perceived exertion, given the external loads applied in training and competitions. Evaluate the variations in temperature and in the subjective perception of effort during preparatory training for the Gaucho Futsal League, in the 2020 season. The sample consisted of 19 male futsal players. In this study, to verify the impact of external training loads, body temperature was measured and the subjective perception of effort of the individuals in the sample was collected during 15 training sessions. A variation was observed, both in the athletes’ body temperature (35.78°C and 36.25°C), in the different moments of training, and in the subjective effort perception. At the beginning, mean values of 3.12 ± 0.43 were obtained, changing to 4.79 ± 0.28 and, at the end, to 4.87 ± 0.33. These statistical results showed a moderately significant correlation between body temperature and subjective effort perception in warming up. In view of these findings, there was a directly proportional relationship between these variables, such that the increase in body temperature raises the subjective effort perception. In view of the results of this investigation, we infer that the measurement of subjective effort perception is an excellent tool to quantify and control the loads of a training session in the futsal modality.